Perbezaan kecemerlangan pelajar daripada perspektif pengurusan masa, keputusan akademik terdahulu dan jantina - Azura Hamdan; Rohany Nasir; Rozainee Khairudin; Wan Shahrazad Wan Sulaiman (Penerbit Universiti Kebangsaan Malaysia, 2015)
The purpose of this study was to examine and identify whether factors such as previous academic result (SPM), gender and time management could determine differences among students, based on academic performance or grade point average (GPA). A total of 551 undergraduate students from four universities participated in the study. Students with a GPA of 3.50 or greater significantly differed in their level of time management than those with a GPA of less than 2.50. In terms of gender, female students were found to have higher GPA than male students. However, students enrolled with excellent SPM result did not differ significantly in term of their GPA from students enrolled with low SPM result. Results from ANOVA and t-test showed that time management and gender, not previous academic result, were the important factors to distinguish students with low or high academic performance. The implication of this study showed that academic excellence among undergraduates did not rely solely on previous academic result, but the role of time management and gender did play significant factors in distinguishing high achievers vs low achievers.